Pengaruh Pengungkapan Enterprise Risk Management dan Kinerja Keuangan terhadap Return Saham - Nur Putra Rakhmadani; Fifi Swandari; Ali Sadikin (Jurnal Ekonomi dan Manajemen, 2018)
This study aims to analyze the effect of ERM disclosure, Return On Assets (ROA) and Debt to Equity Ratio (DER) to stock returns on the property firms. Population in this study is 48  property company sub sector of property and real estate industry listed on Indonesia Stock Exchange during the period of 2012 to 2016. The sample method used was purposive sampling and the obtained samples are 33 property companies.The Data were analyzed using multiple linear regression analysis done by SPSS Version Program 23.00 for Windows. The results showed that: (1) Enterprise Risk Management disclosure does not affect the Stock Return. High ERM level does not affect stock return; (2) Return On Asset effect on Stock Return; and (3) Debt to Equity Ratio effect on Stock Return on property companies listed on Indonesia Stock Exchange period 2012-2016.